Development of head and neck pathology in Europe - Hellquist, Henrik; Agaimy, Abbas; Stenman, Göran; Franchi, Alessandro; Nadal, Alfons; Skalova, Alena; Leivo, Ilmo; Zidar, Nina; Simpson, Roderick H W; Slootweg, Pieter J; Hernandez-Prera, Juan C; Ferlito, Alfio (Virchows Archiv, 2022)
This review gives a brief history of the development of head and neck pathology in Europe from a humble beginning in the 1930s to the explosive activities the last 15 years. During the decades before the introduction of immunohistochemistry in the 1980s, head and neck pathology grew as a subspeciality in many European countries. In the late 1940s, the Institute of Laryngology and Otology with its own pathology laboratory was founded in London, and in 1964 the World Health Organization (WHO) International Reference Centre for the Histological Classification of Salivary Tumours was established at the Bland-Sutton Institute of Pathology, also in London. International collaboration, and very much so in Europe, led to the publication of the first WHO Classification of Salivary Gland Tumours in 1972. In the 1960s, a salivary gland register was organised in Hamburg and in Cologne the microlaryngoscopy was invented enabling microscopic endoscopic examination and rather shortly afterwards a carbon dioxide laser attached to the microscope became established and laryngeal lesions could be treated by laser vaporisation. During the last three decades, the use of immunohistochemistry supplemented with cytogenetic and refined molecular techniques has greatly facilitated the pathological diagnostics of head and neck lesions and has had a huge impact on research. Collaboration between different European centres has drastically increased partly due to establishment of scientific societies such as the Head and Neck Working Group (HNWG) within the European Society of Pathology and the International Head and Neck Scientific Group (IHNSG). A very large number of European pathologists have contributed to the 2nd, 3rd and 4th WHO books, and are involved in the upcoming 5th edition. Accredited educational meetings and courses are nowadays regularly arranged in Europe. Numerous textbooks on head and neck pathology have been written and edited by European pathologists. The increased collaboration has created larger series of tumours for research and new entities, mainly defined by their genetic abnormalities, are continuously emerging from Europe, particularly regarding salivary gland neoplasms and "undifferentiated" sinonasal tumours. These findings have led to a better and more precise classification and open the possibilities for new treatment strategies.
Keywords: World Health Organization; Head and neck pathology; Salivary neoplasms; Cancer; Evropa; Europe; Světová zdravotnická organizace; Laryngeal neoplasms; nádory hlavy a krku; Salivary Gland Neoplasms; Sinonasal neoplasms; lidé; Head and Neck Neoplasms; nádory slinných žláz; History of European head and neck pathology; Salivary Glands; Humans; slinné žlázy